Boudins: an useful tool in structural geology teaching - Pamplona, J. (2019)
The boudins are generally finite objects of easy identification in the field. They are excellent structures for learning the measurement of linear and planar structures. Geometric and morphological parameters of the boudins allow drawing conclusions about several structural parameters, such as, kinematics. vorticity, strain rate and shear strain.